Smart Apps Creator-Based Digital Media and Elementary Science Achievement: Evidence from Rural Schools - Fresya Angnelvin Dengkidala; Nurrahma Nurrahma; Rizal Rizal; Sisriawan Lapasere; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
The integration of digital technology in elementary science education remains limited in rural Indonesian schools, where conventional lecture-based instruction predominates and student learning outcomes are suboptimal. This study investigated the effect of Smart Apps Creator-based digital media on fifth-grade students' science learning outcomes at Sintuwulemba State Elementary School, Poso Regency. A quasi-experimental one-group pretest-posttest design was employed with 25 fifth-grade students. Participants completed a validated 20-item multiple-choice achievement test before and after a four-week intervention involving interactive digital media incorporating visual animations, simulations, instructional videos, and formative assessments. Data were analyzed using descriptive statistics and paired-samples t-test. The intervention produced a significant improvement in learning outcomes, with mean scores increasing from 61.56 (SD = 2.45) to 83.04 (SD = 1.70), representing a 34.9% gain (t = 28.63, df = 24, p < 0.001, Cohen's d = 10.21). The intervention proved equally effective across all initial achievement levels, demonstrating no correlation between pretest scores and improvement magnitude. Smart Apps Creator-based digital media significantly enhances elementary science learning outcomes through multimodal content delivery and interactive engagement. These findings support technology integration in rural schools as an equity-enhancing pedagogical strategy, though randomized controlled trials with extended follow-up periods are needed to establish long-term effectiveness and generalizability.